A temperature gradient method for lipid phase diagram construction using time-resolved x-ray diffraction. - CAFFREY, MARTIN (My University, 1987)
A method that enables temperature-composition phase diagram construction at unprecedented rates is described and evaluated. The method involves establishing a known temperature gradient along the length of a metal rod. Samples of different compositions contained in long, thin-walled capillaries are positioned lengthwise on the rod and "equilibrated" such that the temperature gradient is communicated into the sample. The sample is then moved through a focused, monochromatic synchroton-derived x-ray beam and the image-intensified diffraction pattern from the sample is recorded on videotape continuously in live-time as a function of position and, thus, temperature. The temperature at which the diffraction pattern changes corresponds to a phase boundary, and the phase(s) existing (coexisting) on either side of the boundary can be identified on the basis of the diffraction pattern. Repeating the measurement on samples covering the entire composition range completes the phase diagram. These additional samples can be conveniently placed at different locations around the perimeter of the cylindrical rod and rotated into position for diffraction measurement. Temperature-composition phase diagrams for the fully hydrated binary mixtures, dimyristoylphosphatidylcholine (DMPC)/dipalmitoylphosphatidylcholine (DPPC) and dipalmitoylphosphatidylethanolamine (DPPE)/DPPC, have been constructed using the new temperature gradient method. They agree well with and extend the results obtained by other techniques. In the DPPE/DPPC system structural parameters as a function of temperature in the various phases including the subgel phase are reported. The potential limitations of this steady-state method are discussed.
PUBLISHED
Keywords: Atomic, molecular and chemical physics; Electromagnetic radiation; x-ray diffraction